2004
DOI: 10.1001/archpedi.158.4.385
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Physical Activity, and Sedentary Behaviors as Risk Factors for Overweight in Adolescence

Abstract: Of the 7 dietary and physical activity variables examined in this cross-sectional study, insufficient vigorous physical activity was the only risk factor for higher body mass index for adolescent boys and girls. Prospective studies are needed to clarify the relative importance of dietary and physical activity behaviors on overweight in adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
253
7
15

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(313 citation statements)
references
References 37 publications
36
253
7
15
Order By: Relevance
“…76 Low levels of physical activity and greater amounts of sedentary pursuits, in particular television viewing (43 h/ days), during childhood and/or adolescence is predictive of greater future adiposity and or overweight. [77][78][79][80][81][82][83][84] Thus, the rationale for prescribing exercise as an adjunct to dietary restriction is compelling given its potential to reduce overweight-related comorbidity and the hazard associated with dietary restriction alone.…”
Section: Discussionmentioning
confidence: 99%
“…76 Low levels of physical activity and greater amounts of sedentary pursuits, in particular television viewing (43 h/ days), during childhood and/or adolescence is predictive of greater future adiposity and or overweight. [77][78][79][80][81][82][83][84] Thus, the rationale for prescribing exercise as an adjunct to dietary restriction is compelling given its potential to reduce overweight-related comorbidity and the hazard associated with dietary restriction alone.…”
Section: Discussionmentioning
confidence: 99%
“…[49][50][51][52] Some of these studies include objective measures of physical activity, such as accelerometer data. [53][54][55] Null findings are not uncommon. 56,57 One study found that obese youth are more active than nonobese youth.…”
Section: Physical Activity and The Development Of Obesitymentioning
confidence: 99%
“…8 Previous research on physical activity in paediatric obesity has focused on non-clinical samples, comparing habitual physical activity or energy expenditure in obese and nonobese children and adolescents. [9][10][11][12][13][14][15][16] Most of these studies found lower levels of physical activity and *PAL (TEE/REE) in obese children and adolescents relative to their lean counterparts. [9][10][11][12][14][15][16] The few studies that have compared objec-tively measured sedentary behaviour in non-clinical samples of obese and lean children have reported inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] Most of these studies found lower levels of physical activity and *PAL (TEE/REE) in obese children and adolescents relative to their lean counterparts. [9][10][11][12][14][15][16] The few studies that have compared objec-tively measured sedentary behaviour in non-clinical samples of obese and lean children have reported inconsistent results. 10,14,15 The aims of this study were therefore to use accelerometry to (1) measure habitual physical activity and sedentary behaviour objectively in a clinical sample of obese children aged 5-11 years; (2) compare the results with a sample of ageand sex-matched non-obese control children.…”
Section: Introductionmentioning
confidence: 99%